SOCIAL AND ECONOMIC AND LABOUR MARKET REGULATION IN UKRAINE (METHODOLOGICAL ASPECT) - Klochko, O. O. (Science and Transport Progress, 2006)
This article is devoted to methodology of regulation of macroeconomical processes on the labour market.